2023
DOI: 10.3389/fneur.2023.1185554
|View full text |Cite
|
Sign up to set email alerts
|

Thrombectomy with and without computed tomography perfusion imaging for large-vessel occlusion stroke in the extended time window: a meta-analysis of randomized clinical trials

Zheng Zhan,
Feng Gu,
Yi Ji
et al.

Abstract: ObjectiveIn recent years, several studies have used computed tomography perfusion (CTP) to assess whether mechanical thrombectomy can be performed in patients with large-vessel occlusion (LVO) stroke in an extended time window. However, it has the disadvantage of being time-consuming and expensive. This study aimed to compare the impact of the CTP group with the non-CTP group [non-contrast CT (NCCT) ± CT angiography (CTA)] on the prognosis of this patient population.MethodsA search of PubMed, EMBASE, and the C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 42 publications
0
5
0
Order By: Relevance
“…15 of the included studies comprised both a Systematic Review and a Meta-analysis, with the remaining two studies (11,12) consisting of only a systematic review as meta-analysis was not possible due to heterogeneity of the studies. 10 SRs included both randomized controlled studies (RCTs) and observational studies (5,10,11,(13)(14)(15)(16)(17)(18)(19)(20), five included only observational studies (9,11,12,21,22), and two included only RCTs (23,24).…”
Section: Characteristics Of the Included Reviewsmentioning
confidence: 99%
See 2 more Smart Citations
“…15 of the included studies comprised both a Systematic Review and a Meta-analysis, with the remaining two studies (11,12) consisting of only a systematic review as meta-analysis was not possible due to heterogeneity of the studies. 10 SRs included both randomized controlled studies (RCTs) and observational studies (5,10,11,(13)(14)(15)(16)(17)(18)(19)(20), five included only observational studies (9,11,12,21,22), and two included only RCTs (23,24).…”
Section: Characteristics Of the Included Reviewsmentioning
confidence: 99%
“…Five SRs ( 5 , 11 , 15 , 17 , 20 ) addressed the benefits of functional outcomes for strategies to reduce delays in MT, and six SRs ( 5 , 10 , 17 , 20 , 21 , 23 ) addressed strategies to reduce delays in MT in terms of time-related outcomes. The most frequently reported strategy that was assessed in four SRs was “Direct to angio-suite” ( 5 , 15 , 17 , 20 ).…”
Section: Findings Of the Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…However, a significant proportion of AIS-LVO patients, estimated to be approximately 30-40%, present to care facilities beyond this traditional window, specifically between 6 and 24 h from symptom onset (Jadhav et al, 2018;Gunda et al, 2021). While the DEFUSE 3 (Endovascular therapy following imaging evaluation for ischemic stroke 3) and DAWN (Diffusion-weighted imaging or computerized tomography perfusion assessment with clinical mismatch in the triage of wake up and late presenting strokes undergoing neurointervention with Trevo) trials have indicated the potential benefits of MT in this extended time window, they also highlighted the variability in outcomes (Jabal et al, 2023;Zhan et al, 2023), with beneficial functional outcomes at 90 days observed in roughly 45 and 49% of patients, respectively (Albers et al, 2018;Nogueira et al, 2018). This variation in outcomes suggests that successful reperfusion does not guarantee favorable recovery for a significant proportion of patients undergoing MT (Campbell et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Five SRs (5,11,15,17,20) addressed the benefits of functional outcomes for strategies to reduce delays in MT, and six SRs (5,10,17,20,21,23) addressed strategies to reduce delays in MT in terms of time-related outcomes. The most frequently reported strategy that was assessed in four SRs was "Direct to angio-suite" (5,15,17,20).…”
Section: In-hospital Transfermentioning
confidence: 99%